ON THE HIERARCHY OF THE CRIMINAL LAW PRINCIPLES WHEN PERFORMING THE TELEOLOGICAL INTERPRETATION IN THE CRIMINAL LAW - Ristivojević, Branislav (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
When determining the goal i.e. the purpose of the legal provisions in the process of interpretation, legal principles are used in all the fields of law. Their role in this procedure is extremely important because they constitute the least common denominator of all the provisions pertaining to the certain law i.e. to the certain field of law, and therefore they may be used for the interpretation of their goal. Since criminal law consists of several legal principles, the science made a hierarchy or list of priority among them, in which the principle of legality is on the first place, while all the others are second ranked or are neglected. In this paper the author disrupted this hierarchy of criminal law principles by criticizing the reasons that led to it and by pointing to their obsoleteness and being out of dated. As much as legality was needed at the time when it was created as a natural companion and guardian of hardly achieved but still unsecure freedom of people, today when the freedom is undisputable, it lost its importance. The possibilities to abuse the criminal law do not lay today in non-written criminal law provisions created to be similar to certain cases that have backward application in time, which create a danger to the citizens’ freedom and which are prevented by the principle of legality. They lay in their value variable dimension which is emphasized when it is interpreted teleological, i.e. by interpreting its goal. And that means that it is interpreted in accordance with its main function – protection of certain values i.e. when the provisions of the Criminal Code related to the purpose of the criminal law and purpose of punishing are (ab) used, and those are the provisions that were shaped by the science in the principle of legitimacy. For this reason it is necessary to change the hierarchy of the criminal law principles when performing the teleological interpretation in the criminal law. The principle of legitimacy shall come to the first place, while the principle of legality shall come to the second place. This will make it difficult to the interpreters of the criminal law to unjustifiably point out that they have satisfied all the condition precedents placed in front of them by the principle of legality, by not mentioning how they are unnecessary since the freedom is today undisputable value, while at the same time they are concealing the wide possibilities of efficient abuse of the principle of legality.